2013
DOI: 10.1088/0004-6256/145/4/100
|View full text |Cite
|
Sign up to set email alerts
|

The Eclipsing System Ep Andromedae and Its Circumbinary Companions

Abstract: We present new long-term CCD photometry for EP And acquired during the period 2007 to 2012. The light curves display total eclipses at primary minima and seasonto-season light variability. Our synthesis for all available light curves indicates that the eclipsing pair is a W-type overcontact binary with parameters of q=2.578, i=83 • .3, ∆T =27 K, f =28 %, and l 3 =2∼3 %. The asymmetric light curves in 2007 were satisfactorily modeled by a cool spot on either of the eclipsing components from a magnetic dynamo. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Lee et al 2014;Hinse et al 2014;Horner et al 2013;Wittenmyer et al 2013;Lee et al 2013;Horner et al 2012). The only well documented exception seems to be the NN Ser system (Beuermann et al 2010;Marsh et al 2014) which presumably hosts a long-term stable system of two Jovian planets involved in the 2:1 MMR or the 5:2 MMR.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 2014;Hinse et al 2014;Horner et al 2013;Wittenmyer et al 2013;Lee et al 2013;Horner et al 2012). The only well documented exception seems to be the NN Ser system (Beuermann et al 2010;Marsh et al 2014) which presumably hosts a long-term stable system of two Jovian planets involved in the 2:1 MMR or the 5:2 MMR.…”
Section: Discussionmentioning
confidence: 99%
“…Applegate model failed to explain the cyclic modulation in the orbital period. Therefore, liking many other contact binaries, e.g., EP And (Lee et al 2013), MR Com (Qian et al 2013) and Li et al (2014), cyclic period variation of V781 Tau is caused by the light travel time effect due to a tertiary. Using the mass function,…”
Section: Discussionmentioning
confidence: 99%
“…The determined parameters for each system are displayed in Table 4, and the corresponding synthetic light curves, solid black lines, are plotted in Figure 3. We found that some of the targets manifest asymmetric light curves, in these cases spot model was applied to fit their light curves (e.g., Qian et al 2007;Lee et al 2013;Zhou et al 2016a). In addition, the search of a third light (l 3 ) was carried out for every system.…”
Section: Photometric Solutionsmentioning
confidence: 99%